2020
DOI: 10.3892/ol.2020.12249
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑623 inhibits tumor progression and is a predictor of poor prognosis of breast cancer

Abstract: Dysregulated microRNAs (miRNAs) serve vital roles in the progression and prognosis of breast cancer. miR-623 has been reported to influence the progression of numerous other cancers, such as lung adenocarcinoma and hepatocellular carcinoma, however, its role in breast cancer remains unclear. In the present study, the mRNA expression of miR-623 was studied in 121 pairs of breast cancer and adjacent normal tissues and cultured cell lines by reverse-transcription quantitative PCR. The association between miR-623 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…41 miR-623 was also shown to suppress invasion of BC in vitro. 42 In this study, we demonstrated that BM TNBC cells express lower levels of miR-623 compared to their parental cells. Silencing miR-623 in TNBC cells with low BM propensity induces MMP1 expression.…”
Section: Microrna Key Regulators Of Mmp1 Expression As Potential Biom...mentioning
confidence: 60%
“…41 miR-623 was also shown to suppress invasion of BC in vitro. 42 In this study, we demonstrated that BM TNBC cells express lower levels of miR-623 compared to their parental cells. Silencing miR-623 in TNBC cells with low BM propensity induces MMP1 expression.…”
Section: Microrna Key Regulators Of Mmp1 Expression As Potential Biom...mentioning
confidence: 60%
“…Studies have shown that the role of hsa-miR-623 as a tumor suppressor has been confirmed, such as targeting the effect of XRCC5 to inhibit the proliferation and metastasis of cancer cells such as breast cancer and liver cancer [ 49 ], inhibit the proliferation of gastric cancer cells, and increase the drug sensitivity of 5-fluorouracil by targeting cyclin D1 [ 50 ]. At the same time, hsa-miR-623 may be used as a predictor of the poor prognosis of breast cancer [ 51 ]. What attracts our particular attention is that the interaction between hsa-miR-623 and colon cancer has never been reported and the exosomes, as the source of hsa-miR-623, have never been studied.…”
Section: Discussionmentioning
confidence: 99%
“…All of which indicated that these NP tissues could be regarded as the normal controls. However, it is still necessary to determine that miR-623 expression in NP tissues were not affected by the spinal tumor microenvironment, as it has been reported that miR-623 is a tumor suppressor and its expression may change in tumor patients [ 28 30 ]. Finally, although the essential role of the HIF-1 α -miR-623-TXNIP pathway was observed in regulating apoptosis and inflammatory responses induced by oxidative stress in NP cells, it must be noted that the findings were collected from the experiment results within normal NP cells.…”
Section: Discussionmentioning
confidence: 99%